Maintaining Military Medical Skills During Peacetime Outlining and Assessing a New Approach - Eibner, Christine (RAND Corporation, 2008)
Military medical personnel are tasked with fulfilling both the benefits mission and the readiness mission of the U.S. Department of Defense (DoD). However, the medical skills required during deployment are likely to differ significantly from those required during peacetime. This study explored an arrangement in which some personnel are stationed in nonmilitary settings where the case mix might more closely resemble that expected under deployment.